PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR - Rohmah, Wafrotur (Jurnal Pendidikan Ilmu Sosial, 2014)
The aim of the research is to know futher about the influence between parent socialeconomics condition and parent attention towards students study achievement, bothpartially or simultantly. The kinds of research is quantitative with this explanative approachused all students from class XI IPS SMA Negeri 1 Purwantoro in 2013/2014 Academic Year,around 103 students as population. Research sample around 78 students was established byusing sampling technique proportional random sampling. Technique of Data collection byusing questionaire and documentation, then data analysis by using doubled linierregression.The research result show that parent social economics condition and parentattention both partially or simultantly have positive influenced towards study achievement ofstudents from class XI IPS SMA Negeri 1 Purwantoro in 2013/2014 Academic Year, theeffective contribution of parent economics condition is 32,2%, while the effective contributionof parent attention is 22,8%, therefore total contribution of both is 55%.